2020
DOI: 10.3390/cancers12020487
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells and Metabolic Parameters in NSCLC Patients Treated with Checkpoint Inhibitors

Abstract: Circulating tumor cells (CTC) count and characterization have been associated with poor prognosis in recent studies. Our aim was to examine CTC count and its association with metabolic parameters and clinical outcomes in non-small cell lung carcinoma (NSCLC) patients treated with immune checkpoint inhibitors (ICI). For this prospective study, data from 35 patients (23 males, 12 females) were collected and analyzed. All patients underwent an 18F-fluorodeoxyglucose positron emission tomography/computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…This is in line with a recent study of Vecchiarrelli and colleagues, who demonstrated a positive correlation between sPD-L1 levels and metastatic sites [ 13 ]. Even though this finding need to be confirmed in a larger cohort, the combination of sPD-L1 levels along with metabolic parameters could be useful for treatment optimization, allowing to identify non-responder patients already at baseline, as demonstrated by our group and others [ 14 , 15 ]. Previously, we have documented the potential prognostic role of combined sPD-L1 and metabolic parameters already in NSCLC candidate patients of surgery [ 16 ].…”
Section: Discussionmentioning
confidence: 64%
“…This is in line with a recent study of Vecchiarrelli and colleagues, who demonstrated a positive correlation between sPD-L1 levels and metastatic sites [ 13 ]. Even though this finding need to be confirmed in a larger cohort, the combination of sPD-L1 levels along with metabolic parameters could be useful for treatment optimization, allowing to identify non-responder patients already at baseline, as demonstrated by our group and others [ 14 , 15 ]. Previously, we have documented the potential prognostic role of combined sPD-L1 and metabolic parameters already in NSCLC candidate patients of surgery [ 16 ].…”
Section: Discussionmentioning
confidence: 64%
“…In melanoma‐treated patients, changes in CTC counts precede standard clinical assessment and are highly predictive of long‐term clinical outcomes 38 . In nonsmall cell lung carcinoma (NSCLC)‐treated patients, elevated CTCs count correlates with highly glycolytic tumors that can potentially metastasize at distant sites 39 …”
Section: Ctcs Clinical Applicationmentioning
confidence: 99%
“…In conclusion, despite the more effective way of assessing the [ 18 F]FDG PET-based response in patients treated with ICPIs, available studies suggest that [ 18 F]FDG PET can support decision-making about the continuation/discontinuation of therapy, as it can open several windows able to capture different aspects associated with the effect of treatment (i.e., pseudoprogression, hyperprogression, and IRAE) [56]. Table 2 reports the characteristics of published studies involving the use of [ 18 F]FDG PET to assess the response to ICI [46][47][48]50,51,54,[57][58][59][60][61][62][63][64][65][66][67][68]. Figure 2 shows a representative example of baseline and post-treatment [ 18 F]FDG PET in a patient with advanced NSCLC treated with Nivolumab.…”
Section: Pet-based Response To Icpis In Patients With Nsclcmentioning
confidence: 99%